The Foreign Relations of Ugarit - Weber, Carl Philip (1966)
Ph.D.; University Microfilms Order No. 66-13,666. Microfilm $3.00; Xerography $9.90; Dissertation Abstracts 27/9 (Ann Arbor, Mich., March 1967) 2969-A.